Efforts to Improve Student Learning Outcomes with the Team Group Tournament Model in Islamic Education Learning at SLB Negeri 1 Lima Kaum - Wardila, Ance Oktavia (MADINA : Journal of Islamic Studies, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using a cooperative model of the team group tournament type. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of special schools. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the cooperative model of the team group tournament type can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.71%, the first cycle 64.33% and in the second cycle it increased to 87.63%. Thus, the use of the cooperative model of the team group tournament type can be used as an alternative to improve student learning outcomes in Islamic religious education learning.